2021
DOI: 10.1111/gcb.15812
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physiological traits conferring tolerance to ocean acidification in mesophotic corals

Abstract: The integrity of coral reefs worldwide is jeopardized by ocean acidification (OA). Most studies conducted so far have focused on the vulnerability to OA of corals inhabiting shallow reefs while nothing is currently known about the response of mesophotic scleractinian corals. In this study, we assessed the susceptibility to OA of corals, together with their algal partners, inhabiting a wide depth range. We exposed fragments of the depth generalist coral Stylophora pistillata collected from either 5 or 45 m to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 110 publications
(181 reference statements)
1
8
0
Order By: Relevance
“…It would seem that coral planulae may be less successful in migrating from deeper habitats to shallow ones and establishing there, than the other way around (Prada & Hellberg, 2021; Rippe et al, 2021; Serrano et al, 2014; Shlesinger & Loya, 2021). Indeed, the current findings are consistent with several studies suggesting that population connectivity along depth may be relevant only for some depth‐generalist species but not for all, or not in all biogeographic regions (Bongaerts et al, 2017; Drury et al, 2020; Liberman et al, 2018; Rippe et al, 2021; Scucchia et al, 2021; Serrano et al, 2014; Shlesinger et al, 2018; Shlesinger & Loya, 2021). Taken together with our findings of reduced reproductive activity at mesophotic depth, it seems less likely that migrating into the deeper MCEs can provide corals with a long‐term viable refuge that will enable them to successfully replenish and sustain shallow‐water populations.…”
Section: Discussionsupporting
confidence: 91%
“…It would seem that coral planulae may be less successful in migrating from deeper habitats to shallow ones and establishing there, than the other way around (Prada & Hellberg, 2021; Rippe et al, 2021; Serrano et al, 2014; Shlesinger & Loya, 2021). Indeed, the current findings are consistent with several studies suggesting that population connectivity along depth may be relevant only for some depth‐generalist species but not for all, or not in all biogeographic regions (Bongaerts et al, 2017; Drury et al, 2020; Liberman et al, 2018; Rippe et al, 2021; Scucchia et al, 2021; Serrano et al, 2014; Shlesinger et al, 2018; Shlesinger & Loya, 2021). Taken together with our findings of reduced reproductive activity at mesophotic depth, it seems less likely that migrating into the deeper MCEs can provide corals with a long‐term viable refuge that will enable them to successfully replenish and sustain shallow‐water populations.…”
Section: Discussionsupporting
confidence: 91%
“…Such stimulation can enhance host fitness under acidification (Guillermic et al, 2021). In this study, the enrichment of terms related to coral oxidative stress under pH 7.6 (low; Table S5) suggests increased photosynthetic activity in the endosymbiotic algae due to the higher availability of CO2 in seawater, as observed in the endosymbionts of Stylophora pistillata primary polyps and adults (Scucchia et al, 2021a;Scucchia et al, 2021b). It has been hypothesized that at higher concentrations of CO2 the stimulation of symbiont photosynthesis could prevent acidosis of the host cells, thus helping with preserving cellular acid-base homeostasis (Gibbin et al, 2014), and ultimately alleviating the effects of OA on the host fitness, as observed here in planula developing at pH 7.3.…”
Section: Symbiont Stimulation Under High Co2mentioning
confidence: 55%
“…Genes involved in calcium ion binding like calreticulin provide structural and cell adhesion functions that aid in the biomineralization process (Mass et al, 2016) and may be upregulated to compensate for the chemical shift in carbon equilibrium in the seawater (Comeau et al, 2018;DeCarlo et al, 2018;Zhao et al, 2020). However, upregulation of these genes in response to OA may increase energetic demand, as observed in some adult (Davies et al, 2016;Vidal-Dupiol et al, 2013;Scucchia et al, 2021b). This increased demand could potentiate the rapid depletion of larval lipid stores if the energy derived from their endosymbionts is insufficient to keep up with demand (Alamaru et al, 2009;Ben-David-Zaslow and Benayahu, 2000;Harii et al, 2010), ultimately decreasing larval size.…”
Section: Outcomes Of Developing In Low Phmentioning
confidence: 99%
“…This pattern was accompanied by enrichment of terms associated with amino acid catabolism, suggesting A. cervicornis may have mediated physiological stress through protein catabolism (Davies et al, 2016; Aguilar et al, 2019; Rädecker et al, 2021). While we did not assess host or symbiont physiological traits along with these gene expression profiles, it is likely that the growth and/or energy reserves may have been impacted as a result of treatment conditions (Aichelman et al, 2021; Scucchia et al, 2021; Bove et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%